2023
DOI: 10.1001/jamanetworkopen.2023.4066
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Online-Onboard Adaptive Intensity-Modulated Radiation Therapy or Volumetric-Modulated Arc Radiotherapy With Image-Guided Radiotherapy for Patients With Gynecologic Tumors in Dependence on Fractionation and the Planning Target Volume Margin

Abstract: ImportancePatients with newly diagnosed locally advanced cervical carcinomas or recurrences after surgery undergoing radiochemotherapy whose tumor is unsuited for a brachytherapy boost need high-dose percutaneous radiotherapy with small margins to compensate for clinical target volume deformations and set-up errors. Cone-beam computed tomography–based online adaptive radiotherapy (ART) has the potential to reduce planning target volume (PTV) margins below 5 mm for these tumors.ObjectiveTo compare online ART te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Guberina et al 2023 found that non-adapted treatments resulted in a median CTV coverage loss of 11.4%, whereas adapted treatments only had a loss of 0.6%. No grade 3 toxicity events were observed during the study, which had a median follow-up period of 4 months [ 10 ].…”
Section: Clinical Results Of Artmentioning
confidence: 99%
See 2 more Smart Citations
“…Guberina et al 2023 found that non-adapted treatments resulted in a median CTV coverage loss of 11.4%, whereas adapted treatments only had a loss of 0.6%. No grade 3 toxicity events were observed during the study, which had a median follow-up period of 4 months [ 10 ].…”
Section: Clinical Results Of Artmentioning
confidence: 99%
“…Over the past many decades, radiotherapy has evolved in sophistication to achieve increasingly improved accuracy and precision. With these advancements, handling daily anatomical changes through ART became necessary owing to the capability to conformally and accurately target the tumor and the ever-shrinking margins [ 9 , 10 ].…”
Section: Evolution Of Radiotherapy and Why We Need Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The first results in cervical cancer patients demonstrated the feasibility and dosimteric benefits of the ETHOS radiotherapy system [25][26][27][28]. However, these studies were partly from in silico trials, and clinical results are still missing.…”
Section: Discussionmentioning
confidence: 99%
“…While automatic contouring of organs at risk (OAR) has been extensively examined and is increasingly established in radiation therapy departments [1], the automatic delineation of targets remains a significant challenge, even in the context of online onboard Diagnostics 2024, 14, 28 2 of 10 adaptive planning [2]. Accurate target definition requires expertise to convert recommendations and clinical information into a high precision treatment plan.…”
Section: Introductionmentioning
confidence: 99%